Preparation method of high-purity fused quartz powder
Through the methods of cyclic pickling and repeated magnetic separation, the existing fused silica powder process and high product impurities are solved, and the purity and quality of the product are significantly improved.
Patent Information
- Application Number
- CN202411645179.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-14
AI Technical Summary
The existing process for making fused silica powder is relatively cumbersome, and the product has high impurities and low product quality.
The purity of quartz powder is improved by selecting appropriate pickling conditions and magnetic separation field strength by removing metal impurities and magnetic impurities.
Effectively remove metal impurities and magnetic impurities, improve product purity and quality, and solve the problems of cumbersome processes and high product impurities.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz sand, in particular to a method for preparing high-purity fused quartz powder. Background Art
[0002] Fused quartz material has achieved very good results in precision casting shells, especially in the surface layer of silica sol shells. It has made great breakthroughs in the use and price ratio of zircon materials and is an ideal material for engineering applications. Fused quartz is made by melting natural high-purity silicon dioxide in an electric furnace at a temperature above 1760℃ and then rapidly cooling it. This process converts crystalline silicon dioxide into amorphous glass melt. The melting temperature of fused quartz is about 1713℃, the thermal conductivity is low, and the thermal expansion coefficient is almost the smallest among all refractory materials, so it has extremely high thermal shock stability. Therefore, during the roasting and pouring process, the fused quartz shell rarely breaks due to temperature changes. It is an ideal refractory material for investment casting. It can be used as a refractory material for surface or back layer coating, as well as a sanding material. Fused quartz will partially or fully improve the performance of the shell. The small thermal expansion coefficient of fused quartz is conducive to preventing the shell from cracking and deforming during the dewaxing and roasting process, and is conducive to ensuring the stability of the casting size. Fused quartz has high purity and good stability of the coating. The high temperature creep resistance of the shell is improved. The thermal conductivity of fused quartz is poor at low temperature, and the heat capacity is small, only half of that of zircon sand. Most metal liquids have poor wettability to it, which makes it easy to have a gap between the metal solidification layer and the inner surface of the shell, and the thermal conductivity is further reduced, which is conducive to the filling of thin-walled castings. At high temperatures, fused quartz has high transparency and can transfer heat through radiation, making its thermal conductivity exceed that of aluminum silicate shells. This makes the casting cool faster and it is easier to obtain a sound casting.
[0003] The existing process for making fused quartz powder is relatively complicated, and the product has high impurities and low product quality. To address these problems, we propose a method for preparing high-purity fused quartz powder. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-purity fused quartz powder, which solves the problems that the existing process for preparing fused quartz powder is relatively complicated, the impurities in the product are relatively high, and the product quality is relatively low.
[0005] To solve the above problems, the present invention provides the following technical solution: a method for preparing high-purity fused quartz powder, the specific preparation method comprising the following steps:
[0006] S1, crushing: crushing quartz powder into quartz powder;
[0007] S2, washing the quartz powder fully with water and then removing impurities;
[0008] S3, sending the impurity-removed broken particles into a pickling tank for pickling, until the mass volume ratio of the pickled broken particles to the acid solution in the pickling tank is 1:3;
[0009] S4, the crude product is dissolved in a 2-fold alkaline solution, and then subjected to alkaline washing, followed by ultrasonic cleaning;
[0010] S5, sending the cleaned raw materials into a heating furnace for high-temperature heat treatment;
[0011] S6, repeated magnetic separation: the washed quartz sand particles are magnetically separated by a high field strength magnetic separator, and then sent to a wet mill for grinding to obtain quartz particles with a particle size less than 0.15 mm, and finally sent to a medium field strength magnetic machine for magnetic separation;
[0012] S7, using an impact crusher to further crush the fused quartz sand with a particle size of less than 2 mm, and then sending the fused quartz sand to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain high-purity fused quartz powder.
[0013] As a further preferred embodiment of the present invention, in step S1, an impact crusher is used to further crush the fused quartz sand with a particle size less than 0.8 mm, and then the fused quartz sand is sent to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain raw materials of 100 mesh, 150 mesh, 200 mesh, 325 mesh, 400 mesh, and 600 mesh.
[0014] As a further preferred embodiment of the present invention, in step S2, the raw material stone is sent into a microwave reactor during the impurity removal process, and then nitrogen is introduced, and the flow rate of nitrogen is not less than 3L / min. The temperature control program of the microwave reactor is set to heat the temperature to 780-880°C at a heating rate of 15°C / min, and then keep warm for 0.5-1h.
[0015] As a further preferred embodiment of the present invention, in step S3, the pickling solution is a mixture of hydrochloric acid, sulfuric acid, oxalic acid and hydrofluoric acid, and the mixing ratio is 1:0.8:1.2:0.7. The pickled particles are ultrasonically cleaned 2-4 times, the pickling time is 30-40 minutes, the pickling temperature is 45-55°C, and the ultrasonic frequency is 80-120Hz.
[0016] As a further preferred embodiment of the present invention, in step S4, the alkaline solution is a mixture of 6.5 mol / L sodium hydroxide, 3.5 mol / L potassium nitrate, and 3.5 mol / L sodium bicarbonate deionized water, and the ratio of sodium hydroxide, potassium nitrate, and sodium bicarbonate deionized water is 1:0.7:0.9:1.2; the alkaline solution is mixed under stirring, and the final pH is controlled between 8.5-11.
[0017] As a further preferred embodiment of the present invention, in step S5, heating is performed in a high temperature atmosphere furnace, and the temperature is increased to 1500-1900° C. at a heating rate of 15° C. / min, and then kept warm for 40-60 minutes.
[0018] As a further preferred embodiment of the present invention, in step S6, multiple magnetic separators are used to perform repeated magnetic separation at a field strength of 8000-16000 Gauss, and then the particles are sent to a wet mill for grinding to obtain particles with a particle size less than 0.08 mm, and finally sent to a medium magnetic machine for magnetic separation at a field strength of 4000-5000 Gauss.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The preparation method of high-purity fused quartz powder of the present invention adopts cyclic pickling, selects the optimal pickling conditions such as acid concentration, acid dosage, pickling time, temperature, etc., effectively removes metal impurities and has a good purification effect; repeatedly performs magnetic separation under high and low field strengths, has a good magnetic separation effect, preliminarily and efficiently removes magnetic impurities, and the overall product produced has a high purity. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The utility model provides a technical solution: a method for preparing high-purity fused quartz powder, the specific preparation method comprises the following steps:
[0023] S1, crushing: crushing quartz powder into quartz powder;
[0024] S2, washing the quartz powder fully with water and then removing impurities;
[0025] S3, sending the impurity-removed broken particles into a pickling tank for pickling, until the mass volume ratio of the pickled broken particles to the acid solution in the pickling tank is 1:3;
[0026] S4, the crude product is dissolved in a 2-fold alkaline solution, and then subjected to alkaline washing, followed by ultrasonic cleaning;
[0027] S5, sending the cleaned raw materials into a heating furnace for high-temperature heat treatment;
[0028] S6, repeated magnetic separation: the washed quartz sand particles are magnetically separated by a high field strength magnetic separator, and then sent to a wet mill for grinding to obtain quartz particles with a particle size less than 0.15 mm, and finally sent to a medium field strength magnetic machine for magnetic separation;
[0029] S7, using an impact crusher to further crush the fused quartz sand with a particle size of less than 2 mm, and then sending the fused quartz sand to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain high-purity fused quartz powder.
[0030] In step S2, an impact crusher is used to further crush the fused quartz sand with a particle size less than 0.8 mm, and then the fused quartz sand is sent to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain raw materials of 100 mesh, 150 mesh, 200 mesh, 325 mesh, 400 mesh, and 600 mesh.
[0031] In step S2, during the impurity removal process, the raw material stone is sent into a microwave reactor, and then nitrogen is introduced, and the flow rate of nitrogen is not less than 3L / min. The temperature control program of the microwave reactor is set to heat up to 780-880°C at a heating rate of 15°C / min, and then keep warm for 0.5-1h.
[0032] In step S3, the pickling solution is a mixture of hydrochloric acid, sulfuric acid, oxalic acid and hydrofluoric acid, and the mixing ratio is 1:0.8:1.2:0.7. The pickled particles are ultrasonically cleaned 2-4 times, the pickling time is 30-40 minutes, the pickling temperature is 45-55°C, and the ultrasonic frequency is 80-120Hz.
[0033] In step S4, the alkaline solution is a mixture of 6.5 mol / L sodium hydroxide, 3.5 mol / L potassium nitrate, and 3.5 mol / L sodium bicarbonate deionized water, and the ratio of sodium hydroxide, potassium nitrate, and sodium bicarbonate deionized water is 1:0.7:0.9:1.2; the alkaline solution is mixed under stirring, and the final pH is controlled between 8.5-11.
[0034] In step S5, heating is performed in a high temperature atmosphere furnace at a heating rate of 15°C / min to a temperature of 1500-1900°C, followed by heat preservation for 40-60 minutes.
[0035] Step S6, multiple magnetic separators are used to perform repeated magnetic separation at a field strength of 8000-16000 Gauss, and then the particles are sent to a wet mill for grinding to obtain particles with a particle size less than 0.08 mm, and finally sent to a medium magnetic machine for magnetic separation at a field strength of 4000-5000 Gauss.
[0036] Example 1
[0037] A method for preparing high-purity fused quartz powder, the specific preparation method comprising the following steps:
[0038] Crushing: crush the quartz powder into quartz powder, and use an impact crusher to further crush it into fused quartz sand with a particle size of less than 0.8mm, and then send the fused quartz sand to the production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain raw materials of 100 mesh, 150 mesh, 200 mesh, 325 mesh, 400 mesh, and 600 mesh; wash the quartz powder with water, and then remove impurities. During the impurity removal process, send the raw material stone into a microwave reactor, and then introduce nitrogen. The flow rate of nitrogen is not less than 3L / min. The temperature control program of the microwave reactor is set to 15℃ / min. The heating rate is raised to 880°C, and then kept warm for 1h; the impurity-removed broken particles are sent to the pickling tank for pickling, and the mass volume ratio of the pickled broken particles to the acid solution in the pickling tank is 1:3, and the pickling solution is a mixture of hydrochloric acid, sulfuric acid, oxalic acid, and hydrofluoric acid, and the mixing ratio is 1:0.8:1.2:0.7. The particles after pickling are ultrasonically cleaned 4 times, the pickling time is 40min, the pickling temperature is 55°C, and the ultrasonic frequency is 120Hz; the crude product is dissolved in 2 times the alkaline solution, and alkaline washing treatment is carried out. After the treatment, ultrasonic cleaning is carried out, and the alkaline solution is selected A mixture of 6.5mol / L sodium hydroxide, 3.5mol / L potassium nitrate, and 3.5mol / L sodium bicarbonate deionized water, the ratio of sodium hydroxide, potassium nitrate, and sodium bicarbonate deionized water is 1:0.7:0.9:1.2; the alkaline solution is mixed under stirring, and the final pH is controlled between 11; the cleaned raw materials are sent to a heating furnace for high-temperature heat treatment, and the heating adopts a high-temperature atmosphere furnace, and the heating is heated to 1900°C at a heating rate of 15°C / min, and then kept warm for 60 minutes; repeated magnetic separation: the cleaned quartz sand particles are separated by high field strength The quartz particles are then sent to a medium-strength magnetic machine for magnetic separation. Multiple magnetic separators are used for repeated magnetic separation at a field strength of 16,000 Gauss. The particles are then sent to a wet mill for grinding to obtain particles with a particle size of less than 0.08 mm. The particles are then sent to a medium-strength magnetic machine for magnetic separation at a field strength of 5,000 Gauss. An impact crusher is used to further crush the particles into fused quartz sand with a particle size of less than 2 mm. The fused quartz sand is then sent to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain high-purity fused quartz powder.
[0039] Example 2
[0040] A method for preparing high-purity fused quartz powder, the specific preparation method comprising the following steps:
[0041] Crushing: crush the quartz powder into quartz powder, and use an impact crusher to further crush it into fused quartz sand with a particle size of less than 0.8mm, and then send the fused quartz sand to the production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain raw materials of 100 mesh, 150 mesh, 200 mesh, 325 mesh, 400 mesh, and 600 mesh; wash the quartz powder with water, and then remove impurities. During the impurity removal process, send the raw material stone into a microwave reactor, and then introduce nitrogen. The flow rate of nitrogen is not less than 3L / min. The temperature control program of the microwave reactor is set to 15℃ / min. The heating rate is raised to 780°C, and then the temperature is kept for 0.5h; the impurity-removed broken particles are sent to the pickling tank for pickling, and the mass volume ratio of the pickled broken particles to the acid solution in the pickling tank is 1:3, and the pickling solution is a mixture of hydrochloric acid, sulfuric acid, oxalic acid, and hydrofluoric acid, and the mixing ratio is 1:0.8:1.2:0.7. The particles after pickling are ultrasonically cleaned twice, the pickling time is 30min, the pickling temperature is 45°C, and the ultrasonic frequency is 80Hz; the crude product is dissolved in 2 times the alkaline solution, and alkaline washing treatment is carried out. After the treatment, ultrasonic cleaning is carried out, and the alkaline solution is selected Take a mixture of 6.5mol / L sodium hydroxide, 3.5mol / L potassium nitrate, and 3.5mol / L sodium bicarbonate deionized water, the ratio of sodium hydroxide, potassium nitrate, and sodium bicarbonate deionized water is 1:0.7:0.9:1.2; mix the alkaline solution under stirring, and control the final pH value between 8.5; send the cleaned raw materials into a heating furnace for high-temperature heat treatment, and heat them in a high-temperature atmosphere furnace, and heat them to 1500°C at a heating rate of 15°C / min, and then keep them warm for 40 minutes; repeat magnetic separation: use a high field to separate the cleaned quartz sand particles The quartz particles are then sent to a medium-high intensity magnetic separator for magnetic separation and then sent to a wet mill for grinding to obtain quartz particles with a particle size of less than 0.15 mm. The particles are then sent to a medium-high intensity magnetic separator for magnetic separation. Multiple magnetic separators are used for repeated magnetic separation at a field strength of 8000 Gauss. The particles are then sent to a wet mill for grinding to obtain particles with a particle size of less than 0.08 mm. The particles are then sent to a medium-high intensity magnetic separator for magnetic separation at a field strength of 4000 Gauss. An impact crusher is used to further crush the particles into fused quartz sand with a particle size of less than 2 mm. The fused quartz sand is then sent to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain high-purity fused quartz powder.
[0042] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes that fall within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0043] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing high-purity fused quartz powder, characterized in that: The specific preparation method comprises the following steps: S1, crushing: crushing quartz powder into quartz powder; S2, washing the quartz powder fully with water and then removing impurities; S3, sending the impurity-removed broken particles into a pickling tank for pickling, until the mass volume ratio of the pickled broken particles to the acid solution in the pickling tank is 1:3; S4, the crude product is dissolved in a 2-fold alkaline solution, and then subjected to alkaline washing, followed by ultrasonic cleaning; S5, sending the cleaned raw materials into a heating furnace for high-temperature heat treatment; S6, repeated magnetic separation: the washed quartz sand particles are magnetically separated by a high field strength magnetic separator, and then sent to a wet mill for grinding to obtain quartz particles with a particle size less than 0.15 mm, and finally sent to a medium field strength magnetic machine for magnetic separation; S7, using an impact crusher to further crush the fused quartz sand with a particle size of less than 2 mm, and then sending the fused quartz sand to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain high-purity fused quartz powder.
2. The method for preparing high-purity fused silica powder according to claim 1, characterized in that: In step S1, an impact crusher is used to further crush the fused quartz sand with a particle size less than 0.8 mm, and then the fused quartz sand is sent to a production line of a ball mill equipped with an air flow classifier for ball milling and classification to obtain raw materials of 100 mesh, 150 mesh, 200 mesh, 325 mesh, 400 mesh, and 600 mesh.
3. The method for preparing high-purity fused silica powder according to claim 1, characterized in that: In step S2, during the impurity removal process, the raw material stone is sent into a microwave reactor, and then nitrogen is introduced, and the flow rate of nitrogen is not less than 3L / min. The temperature control program of the microwave reactor is set to heat up to 780-880°C at a heating rate of 15°C / min, and then keep warm for 0.5-1h.
4. The method for preparing high-purity fused silica powder according to claim 1, characterized in that: In step S3, the pickling solution is a mixture of hydrochloric acid, sulfuric acid, oxalic acid and hydrofluoric acid, and the mixing ratio is 1:0.8:1.2:0.
7. The pickled particles are ultrasonically cleaned 2-4 times, the pickling time is 30-40 minutes, the pickling temperature is 45-55°C, and the ultrasonic frequency is 80-120Hz.
5. The method for preparing high-purity fused silica powder according to claim 1, characterized in that: In step S4, the alkaline solution is a mixture of 6.5 mol / L sodium hydroxide, 3.5 mol / L potassium nitrate, and 3.5 mol / L sodium bicarbonate deionized water, and the ratio of sodium hydroxide, potassium nitrate, and sodium bicarbonate deionized water is 1:0.7:0.9:1.2; the alkaline solution is mixed under stirring, and the final pH is controlled between 8.5-11.
6. The method for preparing high-purity fused silica powder according to claim 1, characterized in that: In step S5, heating is performed in a high temperature atmosphere furnace at a heating rate of 15°C / min to 1500-1900°C, followed by heat preservation for 40-60 minutes.
7. The method for preparing high-purity fused silica powder according to claim 1, characterized in that: Step S6, multiple magnetic separators are used to perform repeated magnetic separation at a field strength of 8000-16000 Gauss, and then the particles are sent to a wet mill for grinding to obtain particles with a particle size less than 0.08 mm, and finally sent to a medium magnetic machine for magnetic separation at a field strength of 4000-5000 Gauss.
Citation Information
Cited By
Fused quartz finish machining production line integrating multi-stage color sorting and impurity removing
CN121624127A